Effects of sugarcane variety and nitrogen application level on the quality and aerobic stability of sugarcane tops silage - Gu, Qichao; Zhang, Lu; Zhou, Xiaokang; Lin, Bo; Zou, Caixia (Frontiers in Plant Science, 2023)
To better understand the effects of sugarcane variety and nitrogen application level on silage, we analyzed the fermentation quality, microbial community dynamics, and aerobic exposure of sugarcane tops silage from three sugarcane varieties (B9, C22, and T11) treated with three levels of nitrogen (0, 150, and 300 kg/ha urea). After 132 days of silage, the sugarcane tops silage produced from variety B9, with strong nitrogen fixation ability, treated with nitrogen had the highest crude protein (CP) contents, pH, and yeast counts (P < 0.05), as well as the lowest Clostridium counts (P < 0.05), and the CP increased with increasing N application level (P < 0.05). In contrast, the sugarcane tops silage produced from variety C22, with poor nitrogen fixation ability, treated with 150 kg/ha nitrogen had the highest lactic acid bacteria (LAB) counts, dry matter (DM), organic matter (OM) and lactic acid (LA) contents (P < 0.05), as well as the lowest acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents (P < 0.05). However, these results were not present in the sugarcane tops silage produced from variety T11, with no nitrogen fixation ability, whether it was treated with nitrogen or not; although the silage was treated with 300 kg/ha nitrogen, the ammonia-N (AN) content was the lowest (P < 0.05). After 14 days of aerobic exposure, Bacillus abundance increased in the sugarcane tops silage produced from variety C22 treated with 150 kg/ha nitrogen and from varieties C22 and B9 treated with 300 kg/ha nitrogen, while Monascus abundance increased in the sugarcane tops silage produced from varieties B9 and C22 treated with 300 kg/ha nitrogen and from variety B9 treated with 150 kg/ha nitrogen. However, correlation analysis showed that Monascus was positively correlated with Bacillus irrespective of nitrogen level and sugarcane variety. Our results indicated that sugarcane variety C22, with poor nitrogen fixation ability, treated with 150 kg/ha nitrogen produced the highest sugarcane tops silage quality and inhibited the proliferation of harmful microorganisms during spoilage.